Ministério Silas Malafaia: evangelizando à direita (2000-2013) - Koren, Jonas Christmann (2016)
In this research we analyze the work of the pastor and televangelist Silas Malafaia through his television and internet program, between the years of 2000 and 2013, seeking to understand the attempts to conform worldviews among his audience and to influence political guidelines and decisions. Malafaia proposes to his public a political engagement in specific issues, presented as being fundamental to "Christian values", usually of a moral or sexual nature, and defends the positions of an explicit conservatism. It has emerged in recent years as a religious and political leader, not only among the Pentecostal or evangelical public, after publicly opposing the rights and struggles of homosexuals, such as the legal recognition of the stable union of homosexual couples and the criminalization of homophobia. In conjunction with the opposition to homosexuality, the pastor moved into a position of opposition to left-wing parties and movements in general and to denounce supposed communist plans that would be put into practice in the country. We seek with this research to contribute to the understanding of the complex relationship between religion and politics which has been gaining importance in Brazilian society in recent years.KEYWORDS: Silas Malafaia; Religion; Hegemony.